(untitled) (VETERINARIA, 2025)
Formalin, as a proven carcinogenic and toxic chemical, is aiming to be reduced or completely removed from use in all spheres. Among different alternatives for formalin use, the plastination technique is widely known as unique method in tissue preservation. Due to its expensiveness, more affordable method has been invented by Professor Fawzy Elnady. The Elnady technique aims to detoxify formalin specimens used in classes by using cheaper and available chemicals. The specimens obtained are non-toxic, durable, odorless, dry, soft and flexible. They can be used in the teaching of anatomy, but also in other subjects such as embryology, pathology, parasitology, clinics and forensic veterinary medicine. During preparation, formalin is used for tissue fixation, acetone for dehydration, glycerin for impregnation and corn starch for drying of specimens. In this study, we observed effectiveness of the method on more than 100 different specimens. The results showed that lower quality specimens are obtained when the organs are stored in formalin for longer time. Usually, these specimens became darker with the decrease of visibility of structures. Furthermore, we noticed that lungs become darker with tissue sensitive to damages. The liver preparation resulted in dark, non-flexible specimen. We suggest these changes could be due to the time specimens were in glycerin since before this phase specimens had adequate characteristics. Throughout the specimens we also noticed the bad impact organ membranes had if left on the organ. With the acetone, they became too dry and their remains decreased the quality of the specimens. In our study, we confirmed the results of the author but we suggest that this method is not adequate for every type of organ and that organ membranes should be removed prior to process. We emphasize the importance of fresh specimens use, since older formalin specimens after preparation were not of great quality.